Analysis of the Thinking Process of Science Teachers: The Light Absorption Thought Experiment - Uyar, F K; Karamustafaoğlu, O (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
The aim of this research is to investigate the thinking processes of science teachers who are master students in science education regarding the thought experiment designed for the light absorption. For this aim, the phenomenological study method, one of the qualitative research designs, was used. In the study, eight science teachers who were continuing their master were studied by using purposive sampling. Data were collected through interviews on the light absorption thought experiment. Data were collected through face-to-face problem-solving sessions, thinking aloud and backward questioning. From the data, it is seen that the teachers mostly showed secondary effects as establishing a new amount relationship, they carried out thought experiments to conviction, and while they preferred scientific concepts and intuition-based simulations as sources of thinking equally, spatial reasoning-symmetry-compound simulation and experience were preferred equally and less frequently. At the end of the research, it was concluded that the self-efficacy perceptions of the science teachers were high, having a command of the curriculum, having an uneasy mood when solving problems, and having hypothetical thinking skills.